Je kultura tisto, kar nas loči od živali? - Gašperšič, Maja (Monitor ISH, 2005)
Is it really culture that separates us from animals? A catalogue of primate cultures. The paper touches upon one of the most controversial topics of anthropology: the issue of culture in the animal kingdom. Many primate species have been found to engage in practices which are supposed to be tzpically human (especially tool use and gestural communication) and thus the cornerstone of our uniqueness. The paper attempts to derive applicable concepts of culture and the transfer of cultural patterns, which would facilitate a comparative approach to anthropoid cultural traditions. Moreover, it presents a rich array of primate behavioural patterns, which form the cultural repertoires of individual communities.
Keywords: anthropology; antropologija; primatologija; primati; kulturni vzorci; evolucija